Study of hysteroscopy with ultrasonography and its correlation with histopathology in case of abnormal uterine bleeding in perimenopausal and postmenopausal female: a comparative study - Gupta, Shivangi; Hussain, Roshan; Gupta, Himani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Abnormal uterine bleeding (AUB) is a common gynecological problem in perimenopausal and postmenopausal women, requiring accurate evaluation to distinguish benign from premalignant and malignant causes. Ultrasonography (USG) is widely used as an initial screening tool, whereas hysteroscopy provides direct visualization of the uterine cavity. Histopathology remains the gold standard for definitive diagnosis. This study aimed to compare the diagnostic performance of USG and hysteroscopy against histopathology in women presenting with AUB. Methods: A cross-sectional observational study was conducted on 100 women aged ≥40 years presenting with AUB at a tertiary care center. All participants underwent detailed clinical evaluation followed by transabdominal ultrasonography, diagnostic hysteroscopy and endometrial sampling for histopathological examination. Diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and overall accuracy were calculated for USG and hysteroscopy using histopathology as the gold standard. Results: The majority of participants were aged 41–50 years (59%). Menorrhagia was the most common presenting symptom. USG identified endometrial hyperplasia in 10% of patients, whereas hysteroscopy detected hyperplasia in 18%. Histopathology confirmed hyperplasia in 12% and carcinoma in 1% of cases. For diagnosing hyperplasia, USG showed a sensitivity of 83.33% and specificity of 100%, while hysteroscopy demonstrated a sensitivity of 83.33% and specificity of 90.90%. Overall diagnostic accuracy was higher for hysteroscopy. Conclusions: Hysteroscopy demonstrated superior diagnostic capability compared to ultrasonography in detecting endometrial abnormalities, particularly focal lesions. USG remains a useful initial modality; however, hysteroscopy enhances diagnostic precision and should be considered in the evaluation of women with persistent or unexplained AUB.